Predicting the anticancer activity of seconucleoside nitrosourea analogs - Noorbatcha, Ibrahim Ali; Samsudin, Nurhusna; Hamzah, Mohd. Salleh; Idid, Syed Zahir (2009)
Nucleoside can be considered as a specific carrier for the nitrosourea moiety with altered pharmacological properties such as increased water solubility, lower myelotoxicity and increased cell membrane transport. Several seconucleoside nitrosourea analogs have been reported to have anticancer activity against solid tumors such as, Murine adenocarcinomas of the colon 13 (MAC 13), MAC 15A, Colon 38 and mammary carcinoma. In an effort to have a good understanding of the role of the structural features on the anticancer activity of these seconucleosides, we have investigated and obtained Quantitative structure activity relationship (QSAR) involving 26 seconucleoside nitrosourea compounds having anticancer activity against Murine adenocarcinomas of the colon 15A (MAC 15). As it very difficult to obtain the relevant physicochemical properties necessary for QSAR studies, we have made use quantum chemical methods to calculate several electronic and molecular properties of these compounds and used these properties to obtain the best QSAR using statistical procedures. Semiempirical quantum chemical RM1 methods were used to optimize the molecular structures. From the optimized structure hundreds of molecular and electronic properties were calculated and correlated with the anticancer activities of the compounds. The best correlation was obtained using heuristic and multi-linear regression methods. We are able to obtain a best QSAR with correlation coefficient, R2 = 0.8993. We find that that average bond order of oxygen atom and maximum columbic interaction for H-N bond play significant roles in influencing the anticancer activity of the selected compounds. The QSAR obtained in our study can be used to predict the anticancer activity of new seconucleoside nitrosourea analogs, without resorting to any experimental studies.